VARIEDADES DE QUIABEIROS COMO MATÉRIA-PRIMA PARA BIODIESEL - PELEGRINI, ANA KAROLINA (2022)
The demand for energy tends to increase over time and there is a wide diversity of traditional and unconventional plant species in Brazil that can be used as raw materials to biofuel production. Okra (Abelmoschus esculentus) is an unconventional plant that has great potential for oil production applicability. The objective of this work was to evaluate the variability of 35 okra varieties as raw material for biodiesel production. For the genetic analysis study, morpho-agronomic estimates and molecular analyzes were carried out, performing oil extraction with solvent and physical-chemical analyses. Accessions with suitable characteristics were identified, having a good performance according to the application norms. The genotypes showed moderate genetic diversity and low structure, showing the genetic potential of the varieties to obtain superior materials for biofuel production. The oil content found in okra seeds averaged 16.2%, ranging from 13% to 19%. Variety 12 (KA 15) stood out with the best qualities for the analyzed variables.